Anemia is a risk factor for rapid eGFR decline in type 2 diabetes - Xie, Lijie; Shao, Xiaoqing; Yu, Yifei; Gong, Wei; Sun, Fei; Wang, Meng; Yang, Yeping; Liu, Wenjuan; Huang, Xinmei; Wu, Xia; Wu, Huihui; Li, Yiming; et al. (Frontiers in Endocrinology, 2023)
Objective: To investigate the association between anemia and progression of diabetic kidney disease (DKD) in type 2 diabetes. Methods: This was a retrospective study. A total of 2570 in-patients with type 2 diabetes hospitalized in Jinan branch of Huashan hospital from January 2013 to October 2017 were included, among whom 526 patients were hospitalized ≥ 2 times with a median follow-up period of 2.75 years. Annual rate of eGFR decline was calculated in patients with multiple admissions. A rate of eGFR decline exceeding -5 ml/min per 1.73 m2 per year was defined as rapid eGFR decline. The prevalence of DKD and clinical characteristics were compared between anemia and non-anemia patients. Correlation analysis was conducted between anemia and clinical parameters. Comparison of clinical features were carried out between rapid eGFR decline and slow eGFR decline groups. The risk factors for rapid DKD progression were analyzed using logistic regression analysis. Results: The prevalence of anemia was 28.2% among the 2570 diabetic patients, while in patients with DKD, the incidence of anemia was 37.8%. Patients with anemia had greater prevalence of DKD, higher levels of urinary albumin-to-creatinine ratio (UACR), serum creatinine, BUN, urine α1-MG, urine β2-MG, urine NAG/Cr, hsCRP, Cystatin C, homocysteine and lower eGFR, as compared to the patients without anemia. Anemia was correlated with age, UACR, eGFR, urinary NAG/Cr, hsCRP and diabetic retinopathy (DR). Logistic regression analysis of 526 patients with type 2 diabetes during the follow-up period showed that anemia was an independent risk factor for rapid eGFR decline. Conclusion: Anemia is associated with worse renal function and is an independent risk factor for rapid eGFR decline in type 2 diabetes.